Erdheim-Chester Disease as a Mimic of IgG4-Related Disease: A Case Report and a Review of a Single-Center Cohort. Issue 21 (May 2016) - Gianfreda, Davide; Musetti, Claudio; Nicastro, Maria; Maritati, Federica; Cobelli, Rocco; Corradi, Domenico; Vaglio, Augusto
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Immunoglobulin-G4 (IgG4)-related disease (IgG4RD) is a fibro-inflammatory disorder characterized by tissue-infiltrating IgG4 + plasma cells, and, often, high serum IgG4. Several autoimmune, infectious, or proliferative conditions mimic IgG4RD. Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis, characterized by foamy histiocytic infiltration, fibrosis, and chronic inflammation. ECD and IgG4RD manifestations may overlap. A patient presented with huge fibrous retroperitoneal masses causing compression on neighboring structures; the case posed the challenge of the differential diagnosis between IgG4RD and ECD mainly because of a prominent serum and tissue IgG4 response. Retroperitoneal biopsy led to the diagnosis of ECD; the V600E BRAF mutation was found. Treatment with the BRAF inhibitor vemurafenib was started. Treatment failed to induce mass regression and the patient died after 3 months of therapy. Prompted by this case, we examined serum and tissue IgG4 in a series of 15 ECD patients evaluated at our center, and found that approximately one-fourth of the cases have increased IgG4 in the serum and often in the tissue. The differential diagnosis between IgG4RD and ECD can be challenging, as some ECD patients have prominent IgG4 responses. This suggests the possibility of common pathogenic mechanisms between ECD and IgG4RD.